2011
DOI: 10.1186/cc9985
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of ventilation and cardiac related impedance changes with electrical impedance tomography

Abstract: Introduction: Electrical impedance tomography (EIT) has been shown to be able to distinguish both ventilation and perfusion. With adequate filtering the regional distributions of both ventilation and perfusion and their relationships could be analysed. Several methods of separation have been suggested previously, including breath holding, electrocardiograph (ECG) gating and frequency filtering. Many of these methods require interventions inappropriate in a clinical setting. This study therefore aims to extend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 19 publications
4
54
0
1
Order By: Relevance
“…However, similar, sometimes multiple, oppositephase peaks were subsequently found in other animals, e.g., the one presented in Fig. 9, but they were usually much weaker and located outside the heart area as segmented from CT. A similar phenomenon can be observed in the results reported in [10]. We therefore speculate that this effect is associated with the movement of the heart wall at the heart-lung interface.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…However, similar, sometimes multiple, oppositephase peaks were subsequently found in other animals, e.g., the one presented in Fig. 9, but they were usually much weaker and located outside the heart area as segmented from CT. A similar phenomenon can be observed in the results reported in [10]. We therefore speculate that this effect is associated with the movement of the heart wall at the heart-lung interface.…”
Section: Discussionsupporting
confidence: 80%
“…We therefore speculate that this effect is associated with the movement of the heart wall at the heart-lung interface. By comparing with ECG the phase of the weak cardiac frequency observed within the lung ROI (found to be delayed with respect to changes in the heart ROI), it has previously been demonstrated that they represent changes in blood volume [10]. However, the opposite-phase (rather than just delayed) features around the heart, and more specifically the very clear lines which separate them, have not so far been explored (to the best of the authors' knowledge) and may prove a useful feature for further improving the delineation of the heart within thoracic EIT images.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Pour pallier à ce problème, l'analyse des données n'est souvent réalisée que sur les voxels dans lesquels l'écart-type de ΔZ dépasse 20-35 % de son maximum sur l'image d'EIT-f [20] (les voxels dont la variabilité est inférieure sont considérés comme non ventilés, mais peuvent contenir du poumon dérecruté, de la paroi thoracique ou du médiastin). Malgré l'exclusion de ces voxels, le médiastin est souvent inclus dans les régions d'intérêts pulmonaires en raison de la transmission des mouvements respiratoires par contiguïté, et des techniques d'analyse utilisant l'analyse spectrale ont été récemment proposées pour pallier à ce problème [21,22]. Enfin, la TIE ne permet d'explorer qu'une zone limitée du poumon (coupe transversale de 5 cm d'épaisseur environ), dont les caractéristiques évaluées en TIE peuvent différer du reste du parenchyme.…”
Section: Avantages Et Limites De La Tieunclassified
“…Numerous studies have been published in lung function monitoring for adults [1][2][3][4][5][6]. However, assessment of lung function in pediatric population is more challenging due to the patient movements and artifacts which have come under investigation only recently [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%